Approach for Acquiring Multiple Regulatory Requirements for New Information Technology Products in Technical Domains - Filina, Elizaveta; Kamsky, Vladimir; Mohireva, Arina; Badenko, Vladimir (Nurani Hukum, 2025)
This article discusses the development of a new approach to simplify the collection and balancing of regulatory requirements for new IT products in technical domains. The relevance of this topic stems from the complex challenges associated with gathering and managing the requirements from a large number of regulatory documents, particularly in the development of IT products within interdisciplinary fields. This methodology was developed based on existing principles and practices included in the approaches to System engineering and Requirements management approaches. It was tested through a case study in the field of construction survey. And, as a result, the developed algorithm helped to simplify the collection and balancing of regulatory requirements for solving problems in technical subject areas, taking into account the potential of AI technologies application.